Neuropathic pain: from mechanisms to treatment - Finnerup, Nanna B.; Kuner, Rohini; Jensen, Troels Staehelin (Physiological reviews, 2021)
Download figureDownload PowerPoint
First published June 25, 2020
Gesehen am 11.01.2021